Penggunaan model pembelajaran inkuiri terbimbing untuk meningkatkan hasil belajar IPA peserta didik kelas V sekolah dasar - Andini Ramadhanty; Peduk Rintayati; Chumdari Chumdari (Universitas Sebelas Maret, 2023)
This research aims to improve students' science learning outcomes in the matter of changes in temperature and shape of objects. This research is a classroom action research conducted for three cycles. The research subjects were teachers and fifth grade students. The data used were qualitative and quantitative data. Sources of data come from teachers and students, research instruments, and the process of implementing learning. Data collection techniques using tests, observations, interviews, and documentation. Data validity uses triangulation techniques. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and verification, and uses quantitative statistics. The results showed that the percentage of completeness in cycle I was 46.66% on the cognitive aspect, 87.32% on the affective aspect, and 83.33% on the psychomotor aspect. In cycle II it reached 73.33% cognitive aspects, 91.33% affective aspects, and 95.83% psychomotor aspects. In cycle III it reached 87.50% on the cognitive aspect, 96.15% on the affective aspect, and 100% on the psychomotor aspect. The conclusion of the study is that the use of the guided inquiry learning model can improve science learning outcomes material changes in temperature and the shape of objects in fifth grade students. This research provides theoretical and practical implications for students, namely being able to optimize science learning outcomes by using the guided inquiry learning model and students gain learning experience meaningful because they are directly involved in the learning process.